Analisis Hukum Undang-Undang Pemilihan terhadap Pelanggaran Kampanye Ditempat Ibadah dalam Presfektif Equaliy Before The Law - Dadan Ramlan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
General elections for regional heads are a means of democracy to obtain regional heads based on the principles of direct, general, free, confidential, honest and fair elections. In the general election process for regional heads there are 4 (four) types of handling violations, in this case criminal election violations, administrative violations. Elections, Violations of the Code of Ethics and other Violations of Laws, in implementing Violation Handling must pay attention to the principle of equality before the law that all people must be treated equally before the law. This principle is one of the important principles in Indonesia as a rule of law. equality before the law must be implemented There is no exception in the process of handling campaign violations at places of worship during the regional general election process, but in reality there are differences in legal sanctions applied to election participants at the provincial and district or city levels related to campaign violations at places of worship.